Notch Signaling in T Helper Cell Subsets: Instructor or Unbiased Amplifier? - Tindemans, Irma; Peeters, Marlies J. W.; Hendriks, Rudi W. (Frontiers in Immunology, 2017)
For protection against pathogens, it is essential that naïve CD4+ T cells differentiate into specific effector T helper (Th) cell subsets following activation by antigen presented by dendritic cells (DCs). Next to T cell receptor and cytokine signals, membrane-bound Notch ligands have an important role in orchestrating Th cell differentiation. Several studies provided evidence that DC activation is accompanied by surface expression of Notch ligands. Intriguingly, DCs that express the delta-like or Jagged Notch ligands gain the capacity to instruct Th1 or Th2 cell polarization, respectively. However, in contrast to this model it has also been hypothesized that Notch signaling acts as a general amplifier of Th cell responses rather than an instructive director of specific T cell fates. In this alternative model, Notch enhances proliferation, cytokine production, and anti-apoptotic signals or promotes co-stimulatory signals in T cells. An instructive role for Notch ligand expressing DCs in the induction of Th cell differentiation is further challenged by evidence for the involvement of Notch signaling in differentiation of Th9, Th17, regulatory T cells, and follicular Th cells. In this review, we will discuss the two opposing models, referred to as the “instructive” and the “unbiased amplifier” model. We highlight both the function of different Notch receptors on CD4+ T cells and the impact of Notch ligands on antigen-presenting cells.